Rancangan Sistem Knowledge Management Studi Kasus Pada PDPM IBII - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
Institut Bisnis and Informatika Indonesia (IBII) as Indonesian leading business institute has a goal to produce quality graduates who can take part in the global business world. IBII has a commitment to always improve the quality of its graduates by establishing a unit of Capital Markets Data Center (PDPM-IBII) as the development of education in the field of capital market data on the capital market in PDPM-IBII Department can not be optimized and explored so well that there should be a method to manage be stored in a repository of knowledge in a structured order to be communicated and used together as the basic analysis to invest in the stock market. Research carried out a qualitative study which is divided into three stages including: mapping knowledge management, strategy development PDPM-IBII KMS, KMS and development using the Moodle platform. The purpose of this research is to build a knowledge management system to support a culture of sharing knowledgeÂ  in PDPM-IBII in order to develop knowledge management to enhance competitive advantage with the existence ofÂ  KMS PDPM-IBII portal is expected to facilitate the growth of knowledge-sharing culture can create new knowledge that is competitive, the decision system and storage facilities aspirations delivery of electronic documents.